A diarylethene-based "on–off–on" fluorescence sensor for the sequential recognition of mercury and cysteine. Issue 33 (10th April 2017) - Li, Gang; Ma, Lele; Liu, Gang; Fan, Congbin; Pu, Shouzhi
Abstract : A novel photochromic diarylethene with a quinoline unit was synthesized with multi-controllable fluorescence switching properties, which could be induced by light, mercury (Hg 2+ ) and cysteine (Cys). Abstract : A novel photochromic diarylethene with a quinoline unit was synthesized with multi-controllable fluorescence switching properties, which could be induced by light, mercury (Hg 2+ ) and cysteine (Cys). Because the diarylethene displayed obvious fluorescence quenching with Hg 2+ and the fluorescence was recovered to its original state evidently with Cys, it could sequentially recognize Hg 2+ and Cys. Additionally, a logic circuit was constructed with the fluorescence intensity at 468 nm as output, and the combined stimuli of light and chemicals as inputs.